The ‐A2518G polymorphism in the MCP‐1 gene and inflammatory bowel disease risk: A meta‐analysis. Issue 4 (April 2015) - Li, Yu Wen; Yang, Ci Qiu; Xiao, Ying Lian; Li, Jie; Xie, Chen Xi; Zhang, Sheng Hong; Yu, Qiao; Wang, Hui Ling; Lu, Wei Ming; Chen, Min Hu
<x xml:space="preserve">Abstract</x> Objective The monocyte chemoattractant protein‐1 (MCP‐1) ‐A2518G gene polymorphism has been found to be involved in the susceptibility to inflammatory bowel disease (IBD); however, the results of existing studies are controversial. The aim of this meta‐analysis was to assess the relationship between the MCP‐1 ‐A2518G polymorphism and the risk of IBD. Methods PubMed, EMBASE and MEDLINE were searched for studies assessing the relationship between the ‐A2518G polymorphism in MCP‐1 gene and the risk of IBD. Available data were extracted and statistically analyzed using STATA 12.0. Results A total of five publications involving 3137 individuals (1818 IBD cases and 1319 controls) were included in the meta‐analysis. A combined analysis revealed that the MCP‐1 ‐A2518G polymorphism in was a protective factor for GG + AG vs AA (OR 0.76, 95% CI 0.67–0.87, P = 0.000). Subgroup analysis by ethnicity showed that among European patients the AG + GG homozygote, unlike the AA homozygote, had a protective effect against IBD (OR 0.73, 95% CI 0.63–0.84, P = 0.000), but did not do so among Asian and African patients. Subgroup analysis by disease subtype suggested the ‐A2518G polymorphism in MCP‐1 had a protective effect against Crohn's disease (OR 0.69, 95% CI 0.58–0.81, P = 0.000), but not against ulcerative colitis. Conclusions Our meta‐analysis suggested that the ‐A2518G polymorphism in MCP‐1 may be a protective factor for IBD in European populations. Further studies are required to confirm these findings.